Regularization of Singular Systems by Output Feedback (Journal of Computational Mathematics, 2000)
Problem of regularization of a singular system by derivative and proportional output feedback is studied. Necessary and sufficient conditions are obtained under which a singular system can be regularized into a closed-loop system that is regular and of index at most one. The reduced form is given that can easily explore the system properties as well as the feedback to be determined. The main results of the present paper are based on orthogonal transformations. Therefore, they can be implemented by numerically stable ways.
Keywords: Regularization; Singular systems; Output feedback.